Endodontic images as a forensic identification: A literature review (Research, Society and Development, 2021)
Several radiographs are taken during endodontic treatment, thus providing a large number of images with individual characteristics that can be used for forensic identification of an individual. This study aimed to review the literature related to the use of endodontic radiographs in the identification of cadavers. A bibliographic search was carried out in the following databases: PubMed, Scielo, Periódicos Capes, and Web of Science. The keywords used were: forensic dentistry, endodontics, dental radiography, forensic identification. In total, 24 articles related to radiography in the identification of cadavers were found. Among them, 8 studies were selected for including endodontic radiographs for this purpose, comprising different types of studies: case reports of forensic identification through endodontic radiography (4); “in vitro” studies on the influence of high temperatures on endodontic materials and their radiographic images (2); a literature review on how radiographs can be used for identification (1); a comparative study between antemortem and post-mortem endodontic radiographic images (1). Overall, the present study showed that endodontic radiographs have a significant amount of information that can be used to identify a cadaver. Therefore, it is important to perform and store radiographs properly and for long periods. Literature related to the subject is still scarce and further studies are needed.